S FOR SEQUENTIAL: HOW SUPERGIRL PRESERVE HER INTERTEXTUAL CONTINUITY IN THE FILMS - Fauzia Mely Ermanda (UIN Raden Mas Said Surakarta, 2022)
This paper intends to reveal part of myth and its continuity through the female hero whose character is remade all the time and using Hero's theory to analyze. It is using Supergirl film and TV series as the object to reveal the specific myth that frequently appears based on the hero's theory and to see how the film and TV series delivered the character of Supergirl as a female hero. This paper used qualitative methodology and used the words, phrases, and screen capture as the data related to the Supergirl character in the film and TV Series. It is proven by the specific myth that she brings as a female hero and the producer of the film maintained the characteristics of Supergirl that can reflect the specific values that are related to popular culture. The Supergirl film and TV Series have been remade many times, but the writer takes a specific year for comparison and the end can take the red line between the films and TV Series of Supergirl. The result shows that the type of intertextuality found in Supergirl films is its presupposition.